Screening For Prior Exposure to Hepatitis B Virus Infection in Patients Undergoing Chemotherapy - Faheem Ud Din, Babar Ishaq, Talat Ramzan, Muhammad Shuaib, Tahreem Raza, Noor Khajjak (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Chemotherapy in patients with occult hepatitis can lead to the reactivation of Hepatitis B and even acute liver failure in immunosuppressed patients. We investigated the current trend of screening for previous exposure to hepatitis B in patients receiving chemotherapy in Pakistan. Materials and Methods: In this retrospective multicenter study we collected data from the medical records of patients who underwent chemotherapy during a period of six months. Data were collected to assess the screening for Hepatitis before chemotherapy. Results: A total of 182 patients who underwent chemotherapy were studied. The mean age of patients was 52.8 ± 14.9 years; 101(55.5%) were male. 140 (76.9%) were diagnosed with having solid organ malignancies while 42 (23.1%) were reported to have hematological malignancies. In our sample, 103 (56.6%) patients were screened for HBsAg, and amongst these patients, 3 patients tested positive. Hepatitis B core antibody (HBcAb) was checked in only 3 (1.6%) of the patients. The mean level of liver enzymes including ALT, AST, GGT, and ALP were 42.09, 38.98, 63.48 and 138.81, respectively. Ultrasound reports were available for 113 patients and the most common finding was a normal ultrasound 43(38.1%), followed by fatty liver 29 (25.7%). Conclusion: Approximately half of the patients receiving chemotherapy are screened for active hepatitis B infection and screening for occult Hepatitis is almost negligible. Strategies are needed to ensure that all patients receiving chemotherapy should undergo complete screening of Hepatitis B before commencing chemotherapy. Keywords: Occult hepatitis B, HBsAg, HBcAb, Immunosuppression, Chemotherapy.